Population Genetics and Structure of a Global Foxtail Millet Germplasm Collection. Issue 3 (1st November 2015) - Upadhyaya, Hari D.; Vetriventhan, Mani; Deshpande, Santosh P.; Sivasubramani, Selvanayagam; Wallace, Jason G.; Buckler, Edward S.; Hash, C. Tom; Ramu, Punna
Abstract : Foxtail millet [ Setaria italica (L.) P. Beauv.] is one among the most ancient crops of dryland agriculture. It is the second most important crop among millets grown for grains or forage. Foxtail millet germplasm resources provide reservoirs of novel alleles and genes for crop improvement that have remained mostly unexplored. We genotyped a set of 190 foxtail millet germplasm accessions (including 155 accessions of the foxtail millet core collection) using genotyping‐by‐sequencing (GBS) for rapid single nucleotide polymorphisms (SNP) characterization to study population genetics and structure, which enable allele mining through association mapping approaches. After filtering a total 350, 000 raw SNPs identified across 190 germplasm accessions for minor allele frequency (MAF), coverage for samples and coverage for sites, we retained 181 accessions with 17, 714 high‐quality SNPs with ≥5% MAF. Genetic structure analyses revealed that foxtail millet germplasm accessions are structured along both on the basis of races and geographic origin, and the maximum proportion of variation was due to among individuals within populations. Accessions of race indica were less diverse and are highly differentiated from those of maxima and moharia . Genome‐wide linkage disequilibrium (LD) analysis showed on an average LD extends up to ∼150 kbp and varied with individual chromosomes. The utility of the data for performing genome‐wide association studies (GWASs) was tested with plant pigmentation and days to flowering and identified significant marker–trait associations. This SNP data provides a foundation for exploration of foxtail millet diversity and for mining novel alleles and mapping genes for economically important traits.